Temporal and geographical changes in the intestinal helminth fauna of striped dolphins, Stenella coeruleoalba, in the western Mediterranean: a long-term analysis (1982 - 2016) - García-Gallego, Alicia; Raga, Juan Antonio; Fraija-Fernández, Natalia; Aznar, Francisco Javier (Frontiers in Marine Science, 2023)
Temporal and geographical changes in the infections of intestinal helminths of striped dolphins, Stenella coeruleoalba were investigated in waters off the Spanish Mediterranean coast based on a sample of 233 dolphins stranded during 1982-2016. The influence of host-related factors (length and sex) and seasonality were was also examined. Four helminth species had a prevalence > 5%, including adults of three cestodes, i.e, Trigonocotyle globicephalae (prevalence: 5.2%), Tetrabothrius forsteri (94.4%) and Strobilocephalus triangularis (18%); and juveniles of the an acanthocephalan of the genus Bolbosoma (15.9%), further identified as B. capitatum using molecular techniques vasculosum (15.9%). One immature specimen of Diphyllobothrium sp. (Cestoda) was also found in a single dolphin, and two juveniles of Bolbosoma balaenae in two dolphins. Trigonocotyle globicephalae seems to have low specificity for striped dolphins and was only found sporadically. Tetrabothrius forsteri and S. triangularis experienced a slight vs. a strong decrease, followed by a recovery, in infection levels throughout the study period, which are compatible with a reduction in the striped dolphin population caused by the Dolphin Morbillivirus outbreak in 1990. Infections of A molecular analysis suggested that specimens of B. vasculosum actually are juveniles of B. capitatum, a parasite typical from pilot whales, . Infections of this species in striped dolphins suddenly increased in 1990, then vanished. This rapid increase and following decrease are puzzling pattern and can hardly be explained by a single factor. Infections of any helminth species were apparently unaffected byuncorrelated to geographic origin, dolphin sex or season, but parasite load decreased with dolphin length in the case of T. forsteri and S. triangularis. To our knowledge, this study represents the first investigation of multi-decadal changes in cetacean parasites.